Full evaluation of the psychometric properties of COPSOQ II. One-year longitudinal study on Polish human service staff - Łukasz Baka; Monika Prusik; Jan Hyld Pejtersen; Krzysztof Grala (PLoS ONE, 2022)
Purpose The aim of the study was the full evaluation of the psychometric properties of the COPSOQ II in one-year longitudinal study on human service staff in Poland. Data were collected from 599 employees representing three occupational groups related to human service work. Methods CFA was conducted in the structure proposed by the author of the original tool, based on one model, which included 119 observable variables forming 33 latent variables (single item subscales were excluded from analysis). To our knowledge, this was the first complete validation of the entire model using CFA. Reliability analysis was performed using two methods: internal consistency analysis and test-retest analysis. Predictive validity was assessed by correlating COPSOQ II variables with ten criterion variables related to job demands, job resources, work-family conflicts, mental health and well-being. Results According to the results, CFA supported the original structure of the COPSOQ II. Most of the 33 subscales were characterized by good or very good psychometric parameters. The obtained results confirmed also the fairly high reliability, as well as high convergence validity of all subscales of COPSOQ II. Conclusion The final conclusion is that COPSOQ II is characterised by satisfactory psychometric properties and could be successfully used to fulfil the demand for reliable and comprehensive assessment methods also in Polish job market settings.